Defining the endoscopic ultrasound features of chronic pancreatitis in Asians: a multicenter validation study - Koh, Calvin Jianyi; Lakhtakia, Sundeep; Kida, Mitsuhiro; Lesmana, Cosmas Rinaldi A.; Ang, Tiing Leong; Vu, Charles Kieng Fong; Aye, Than Than; Park, Sun Hwa; Almadi, Majid A.; Chong, Charing Ching-Ning; Tang, Raymond Shing Yan; Wu, Xi; Hilmi, Ida; Dhir, Vinay; Pausawasdi, Nonthalee; Basha, Jahangeer; Jin, Zhen-Dong; Yang, Ai Ming; Teoh, Anthony Yuen Bun; Seo, Dong-Wan; Wang, Hsiu-Po; Ho, Khek Yu (Endoscopy, 2020)
Background Although endoscopic ultrasound (EUS) features and criteria have been described in chronic pancreatitis, challenges remain with interoperator variability and ease of adoption. The aim of this study was to define and validate the EUS features of chronic pancreatitis in a multicenter prospective study in Asia.Method The study was divided into two parts: the first part was conducted to derive the EUS features of chronic pancreatitis with adequate interoperator agreement; the second was to prospectively evaluate these features in a multicenter cross-sectional study and determine the optimal combination of features for the diagnosis of chronic pancreatitis. Prospectively enrolled cases had standard internationally validated radiologic or histologic features of chronic pancreatitis, and controls were patients without chronic pancreatitis who underwent EUS examination.Results The top six EUS features that had good interobserver agreement (mean kappa 0.73, range 0.60 – 0.90) were selected to be further evaluated in part II of the study. These included: hyperechoic foci with shadowing, lobularity with honeycombing, cysts, dilated main pancreatic duct, dilated side branches, and calculi in the main pancreatic duct. A total of 284 subjects (132 cases, 152 controls) were enrolled from 12 centers in Asia. All six features had high accuracy ranging from 63.3 % to 89.1 %. Two or more of these six EUS features accurately defined chronic pancreatitis (sensitivity 94.7 %, specificity 98.0 %), with an area under the receiver operating curve of 0.986.Conclusion This multicenter Asian study characterized and defined the EUS features of chronic pancreatitis. This provides a useful tool in clinical practice and further research in pancreatic cancer surveillance.